Pengaruh Health Education Menggunakan Media Audiovisual dan Pamflet Terhadap Pengetahuan Tentang Perilaku Hidup Bersih dan Sehat (PHBS) Pada Anak Usia Sekolah 11-12 Tahun - Dea Permata, Eva; Fatma P, Tiara; Camelia, Dina (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Common health problems in children of this age are often related to poor hygiene and healthy living habits. Efforts that can be made to increase school-age children's knowledge about clean and healthy living behaviors include providing health education using audiovisual media and pamphlets. The type of research used is a pre-experimental design with a one group pre-post test approach. The population in this study consists of school-aged children aged 11-12 years, totaling 100 respondents. This study used the random sampling technique with 80 respondents. The research instrument used was a clean and healthy living behavior questionnaire. Most of the 80 respondents, totaling 60 respondents (75.2%), showed a low level of knowledge, (21.3%) a sufficient level of knowledge, and the post-test results from the 80 respondents, mostly 60 respondents (75.2%), showed a good level of knowledge. The Wilcoxon Sing Rank Test results in SPSS showed a significance value of ? = 0.000 < 0.05, meaning H1 is accepted. This means there is an influence of health education using audiovisual media and pamphlets on the knowledge level of school-aged children aged 11-12 years. The research conclusion shows that there is an influence on the knowledge level about clean and healthy living behaviors in school-aged children aged 11-12 years, with the provision of health education using audiovisual media and pamphlets. It is hoped that future researchers can modify it with other methods.